IMPLEMENTATION OF PBL-HOTS MODEL TO STUDENTS MATHEMATICAL LITERACY SKILL - Aan Hasanah; Dwi Haryanto; Maya Evayanti; Annisa Ul Husnah; Samsudin Samsudin; Rosida Marasabessy (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study was to determine the mathematical literacy ability of students in solving HOTS questions before and after applying the PBL-HOTS model on gradient of perpendicular line. In addition, the purpose of this article is to find out student responses to the PBL-HOTS model learning implemented. This research is descriptive research with a qualitative approach. Data collection techniques were used tests, questionnaires, and documentation. The subjects of this study were 25 students of class VIII SMP Lab school UPI who had high, medium, and low mathematical abilities. This study uses 15 test questions and 19 statements in the questionnaire consisting of 7 negative statements and 12 positive statements. The analysis technique in this study consists of three stages, namely 1) data reduction; 2) data display; 3) drawing conclusions and verification. The results showed that students' mathematical literacy skills in solving HOTS questions before the implementation of PBL-HOTS were 18 students identified as failing, 1 student identified as lacking, 4 students identified as adequate, and 2 students identified as very good. Meanwhile, the students' mathematical literacy skills after implementing the PBL-HOTS model were 9 students identified as failing, 1 less, 8 enough, 3 good, and 4 very good. In addition, from the results of the percentage of students' attitude questionnaires towards the learning carried out, it shows that on average 25 students of class VIII SMP Lab school UPI have a good attitude towards the teaching carried out or on intermediate students like or match learning using the PBL-HOTS model in improving their mathematical literacy ability. The results of this study are expected to be used as information about the mathematical literacy skills of junior high school students. They can be helpful in education, especially mathematics teaching, which can use the PBL-HOTS model in improving the mathematical literacy skills of junior high school students.